Intrajejunal infusion of 2-monoacylglycerol reduced food intake without inducing diarrhea in rats - Chihiro Okuma; Takeshi Ohta; Makoto Ito; Hironobu Tadaki; Tomohiro Oda; Shinichi Kume; Jun Nishiu; Makoto Kakutani (Elsevier, 2016)
Some nutrients, such as carbohydrate, fat and protein, are known to stimulate satiety. However, the effect of sn-2-monoacylglycerol (2-MG), one of the digestive products of triglycerides, on food intake is still unclear. In the present study, the effects of 2-MG on food intake and diarrhea were evaluated and compared with long-chain fatty acid (LCFA) in rats by intrajejunal infusion. Intrajejunal infusion of 2-MG reduced food intake. In addition, 2-MG did not induce diarrhea at the condition that it comparably reduced food intake as compared with LCFA. These results suggest that 2-MG stimulates satiety without inducing diarrhea, different from LCFA.